Tinjauan Angka Kuman dan Sifat Fisik pada Produk Gudeg Wijilan Yogyakarta - Titis Sintya Abela; Supartuti Supartuti; Noor Tifauzah (JURNAL NUTRISIA, 2017)
Background: Yogyakarta is a city that being famous because of gudeg so people call it the city of Gudeg. There is one street in Yogyakarta, which becomes the center of gudeg, namely Wijilan street. Gudeg in Wijilan is close to the main road so it has great possibility to microorganism contamination. Because of that, a research on number of germs in gudeg Wijilan needs to be conducted. Objectives: This research aims to know the food safety level based on the number of germs in gudeg Wijilan, Yogyakarta. Methods: This research was a survey research with cross sectional design. The study was descriptive which describes the safety of gudeg by doing a test on number of germs, physical observation, and observation on condition and sales practice. This research was located in Wijilan street, Yogyakarta. Result: The results showed that the condition and sales practices of gudeg was not hygienic. Physical properties of color, smell, taste and texture of gudeg from 3 gudeg home industries showed differences but it was still safe to consume. The number of germs that was still below the microorganism impurities level came from all gudeg home industries, tofu B and C, young jackfruit vegetable B. The number of germs that was above the microorganism impurities level was found in krecek, chicken and duck egg in all gudeg resturant, young jackfruit vegetable A and C as well as tofu A. Conclusion: Based on the number of germs, it can be concluded that tofu A, young Jackfruit vegetable A, young jackfruit vegetable C, all krecek, all chicken, and all duck eggs are not safe to consume, while from the physical properties of gudeg, all of them were still safe to consume. Keywords: number of germs, physical properties, gudeg